The effects of an intervention program for promoting interorganizational network building between multidisciplinary agencies and community-based organizations: a cluster trial in Japan - Murayama Hiroshi; Yamaguchi Takuhiro; Nagata Satoko; Murashima Sachiyo (BMC, 2012)
Abstract Background Strengthening interorganizational relationships in the community has become an increasingly valued strategy for improving public health in recent years. However, no intervention strategy to foster an interorganizational network in the community has yet been devised. The purpose of this study was to examine the effects on members of an organization of an intervention program designed to promote interorganizational network building between multidisciplinary agencies and community-based organizations (CBOs). Methods The program was conducted in Setagaya and Suginami wards, Tokyo, Japan, for staff of community comprehensive support centers (CCSCs), which are multidisciplinary organizations responsible for the support of the elderly. A cluster non-randomized design with a CCSC as a cluster unit (N = 47) was used. The intervention group comprised 20 centers and the control group 27 centers. Those 27 centers declined to participate in program sessions, but did participate through completing pre- and post-intervention surveys. In total, 158 staff members were eligible to participate in this study, 73 from the intervention group and 85 from the control group. Of the 73 members in the intervention group, 19 participated in the monthly program sessions, over a period of 10 months. Attendees participated in group discussions during the sessions. The effects of the intervention were examined by comparing three groups (attendees and non-attendees of the program from the intervention group, and the control group) and between two groups (intervention group and control group). Results We found no significant difference in any outcome between the intervention group and the control group. However, among the three groups, a significant effect was found in the recognition of knowledge and skills for building networks with CBOs. Recognition of knowledge and skills increased significantly among the attendees compared to non-attendees in the intervention group and the control group. In addition, there was a significant effect, particularly on those with relatively low baseline scores, for the recognition of knowledge and skills. Conclusions The tested intervention proved effective for attendees regarding their recognition of knowledge and skills for promoting interorganizational network building with CBOs.